2013
DOI: 10.1007/s11746-013-2270-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Temperature, Atmosphere and Light on Chemical Stability of Astaxanthin Nanodispersions

Abstract: Astaxanthin, as a functional lipid, can be incorporated easily into different water-based food formulations in the form of a nanodispersion. In this study, astaxanthin nanodispersions were produced using different stabilizer systems, namely, polysorbate 20 (PS20), sodium caseinate (SC), gum arabic (GA) and an optimum combination of these three stabilizers (OPT). Since astaxanthin is sensitive to oxidative damage, its degradations kinetics in the prepared nanodispersion systems were investigated as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
(40 reference statements)
2
19
1
Order By: Relevance
“…The exposure to light in combination with high temperature seemed to make a significant synergistic contribution to the increase in astaxanthin degradation (p \ 0.05). Anarjan and Tan (2013) reported that the k value of astaxanthin degradation was dependent on temperature, atmosphere and illumination conditions. Increasing storage temperature or light intensity increased the k value of loss of astaxanthin nanodispersion.…”
Section: Changes In Astaxanthin In Shrimp Oilmentioning
confidence: 99%
“…The exposure to light in combination with high temperature seemed to make a significant synergistic contribution to the increase in astaxanthin degradation (p \ 0.05). Anarjan and Tan (2013) reported that the k value of astaxanthin degradation was dependent on temperature, atmosphere and illumination conditions. Increasing storage temperature or light intensity increased the k value of loss of astaxanthin nanodispersion.…”
Section: Changes In Astaxanthin In Shrimp Oilmentioning
confidence: 99%
“…Furthermore, the occurrence of cavitation within the homogenizer and the production of free radicals during the nanodispersion preparation procedure along with the high surface area of the nanoparticles for exposure to this aqueous media containing free radicals are other possible causes of the degradation during sample preparation process and storage [2,23]. Addition of antioxidant compounds such as tochopherols to organic phase of nanodispersion systems and removing the oxygen or singlet oxygen generators from sample preparation and storage environment can decrease the astaxanthin degradation considerably [24]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, increasing storage temperature by 10°C resulted in 7-and 24-fold increased astaxanthin oxidation in nanodispersions stabilized by Tween 20 and sodium caseinate, respectively. Similarly, astaxanthin containing nanodispersion exposure to fluorescent/UV light resulted in a respective 3/5-fold increased oxidation for Tween 20 based systems and a 5/ 9-fold increase for sodium caseinate based ones (Anarjan and Tan, 2013c).…”
Section: Emulsification Evaporationmentioning
confidence: 96%
“…(Anarjan et al, 2011b;Anarjan and Tan, 2013b;Cheong and Tan, 2010;Chu et al, 2007b;Tan and Nakajima, 2005). Together with storage conditions, these parameters may also indirectly impact the stability of the encapsulate (Anarjan and Tan, 2013c).…”
Section: Emulsification Evaporationmentioning
confidence: 99%
See 1 more Smart Citation